The Handbook of Clinical Linguistics 2008
DOI: 10.1002/9781444301007.ch10
|View full text |Cite
|
Sign up to set email alerts
|

Chomskyan Syntactic Theory and Language Disorders

Abstract: Reports in Linguistics present ongoing research activities of the members of the Department of Language and Linguistics. The main purpose of the reports is to provide a quick publication outlet. The reports have pre-publication status. The contents, form and distribution of the reports lie in the hands of the authors, and copyright remains with the author(s) of the reports as well. Most of the reports will subsequently appear in revised form as research articles in professional journals or in edited books. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
3
11
0
Order By: Relevance
“…Second, in the self-paced listening task, the children with SLI failed to notice omission of the suffix -t. We conclude that errors with subject-verb agreement in Dutch SLI may also be affected by impaired verb inflection representations, in particular of the -t suffix. The variability observed in our study is in line with Clahsen's (2008) claim that "agreement is not completely absent in SLI, but I the adult agreement paradigm seems to be incomplete with problems focusing on particular forms or verb classes" (p. 177).…”
Section: Causes Of Verb Inflection Errors In Dutch Slisupporting
confidence: 90%
See 1 more Smart Citation
“…Second, in the self-paced listening task, the children with SLI failed to notice omission of the suffix -t. We conclude that errors with subject-verb agreement in Dutch SLI may also be affected by impaired verb inflection representations, in particular of the -t suffix. The variability observed in our study is in line with Clahsen's (2008) claim that "agreement is not completely absent in SLI, but I the adult agreement paradigm seems to be incomplete with problems focusing on particular forms or verb classes" (p. 177).…”
Section: Causes Of Verb Inflection Errors In Dutch Slisupporting
confidence: 90%
“…The observed variation would be compatible with the view that the impairment of agreement is present at the level of lexical knowledge (Clahsen, 2008). More specifically, verb inflection paradigms are incomplete in SLI (Leonard, 2007).…”
Section: Causes Of Verb Inflection Errors In Dutch Slisupporting
confidence: 84%
“…verbs, nouns, adjectives, adverbs and prepositions. The symptoms of agrammatism commonly found in Broca's aphasia [13] such as telegraphic speech, omission of functional morphemes and preservation of content words [14][15][16] were evident in our case. In addition, as reported by Menn and Obler [17,18] regarding the significance of languagespecific features in determining patterns of omission and substitution, along with the general patterns of agrammatism, our study revealed some sorts of language def- icits specific to Kalhori which might be significant to research in aphasiology.…”
Section: Discussionsupporting
confidence: 55%
“…A common pattern can be identified in historically unrelated languages, suggesting difficulties in the conduction of computational operations predicted to be costly regardless of language (Adams, 1990;Friedmann and Novogrodsky, 2004;Jakubowicz, 2004;Leonard et al, 2006;van der Lely and Battell, 2003). At the same time, there are selective impairments suggesting difficulties specific to a syntactic domain (Clahsen, 1999(Clahsen, , 2008Hamann et al, 1998;Marinis and van der Lely, 2007), and cross-language variation that point to problems in the identification of the particular grammatical properties of a language (Leonard, 1992;Bottari et al, 1996;Clahsen et al, 1997;Jakubowicz, 2011;Jakubowicz et al, 1998). This picture of SLI has defied across-the-board explanations centered on either processing or representational difficulties (Leonard, 1989;Gopnik, 1990;Gopnik and Crago, 1991).…”
Section: Introductionmentioning
confidence: 93%